STUDY REGARDING THE ROMANIAN RURAL TOURISM FINANCING AND DEVELOPMENT OPPORTUNITIES - Nicolae BALTEŞ; Alina-Teodora CIUHUREANU (Revista de Turism: Studii si Cercetari in Turism, 2009)
Rural tourism and agricultural tourism are activities, which generate alternative incomes, a fact that offers development possibilities to the rural space, due to the unique landscapes, large semi-natural areas, the inhabitants' born hospitality in the rural surroundings. From this perspective, a modernization, development and innovation process for the Romanian rural tourism is required. All these aspects, however, require financing. Therefore, a pre-accession financing source of the rural tourism was the SAPARD programme, a programme which "offered the opportunity" to many business people to start their business in this field. The paper shows the evolution of the rural boarding houses between 2003-2007, with analyses on the number, type of financing, development region.